2017
DOI: 10.1007/s12639-017-0891-9
|View full text |Cite
|
Sign up to set email alerts
|

Host pregnancy influences the establishment of Trichinella zimbabwensis in Balb C mice

Abstract: In order to determine the effect of host pregnancy in the establishment of , 120 female Balb C mice were divided into 4 groups of 30 mice each. Group 1 animals were orally infected with 50 larvae per gram (LPG) of body weight on day 0; group 2 were mated on day 0 and not infected; group 3 were mated at day 0 and infected with 50 LPG at day 7 post-mating and Group 4 were control animals which were neither mated nor infected. Six animals from each group were sacrificed and the number of adult parasites in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Therefore, the enteric phase of T. zimbabwensis infection majorly favoured a mixed Th1- and Th2-type response, as opposed to T. spiralis and T. pseudospiralis infections which favoured a low-level Th1-type response with an earlier Th2-type response (Wakelin et al, 1994). The role of T cells in both parasites has been fully elucidated (V. Fabre et al, 2009) and the differences in immune responses observed between the encapsulating and the non-encapsulating Trichinella species may be attributed to the challenge dose, parasite antigenic diversity, animal-host sex and the rate of worm expulsion (Furze & Selkirk, 2005; Fu et al , 2009; Hlaka et al , 2015). The mixed Th1- and Th2-type responses elicited create a pro-inflammatory and anti-inflammatory environment that favours parasite immune evasion and establishment (Hewitson et al , 2009; Gruden-Movsesijan et al , 2011; Ilic et al , 2011; Sofronic-Milosavljevic et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the enteric phase of T. zimbabwensis infection majorly favoured a mixed Th1- and Th2-type response, as opposed to T. spiralis and T. pseudospiralis infections which favoured a low-level Th1-type response with an earlier Th2-type response (Wakelin et al, 1994). The role of T cells in both parasites has been fully elucidated (V. Fabre et al, 2009) and the differences in immune responses observed between the encapsulating and the non-encapsulating Trichinella species may be attributed to the challenge dose, parasite antigenic diversity, animal-host sex and the rate of worm expulsion (Furze & Selkirk, 2005; Fu et al , 2009; Hlaka et al , 2015). The mixed Th1- and Th2-type responses elicited create a pro-inflammatory and anti-inflammatory environment that favours parasite immune evasion and establishment (Hewitson et al , 2009; Gruden-Movsesijan et al , 2011; Ilic et al , 2011; Sofronic-Milosavljevic et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Anzaldúa et al [ 16 ] studied the highest level of P4 that causes resistance against parasite invasion during pregnancy. Physiologically, the association between the increase in the P4 doses and induction of NBL mortality was observed in T. spiralis and Trichinella zimbabwensis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although oestrogen was reported to have an effect on establishment of Trichinella infection and reduction of larval burden, these observations have been recorded during pregnancy . In vitro studies have also reported the death of newborn larvae on exposing them to the sera of human pregnant females, though the absence of anti‐NBL antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…() supported such postulation when female rats started to develop more T. spiralis worms and larvae after ovariectomy . Hlaka et al . stressed this point even on another species of Trichinella , when female rats and pregnant mice infected with developed least T. zimbabwensi parasitic burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation